DENTAL CARIES STATUS IN HIGH-RISK PREGNANT WOMEN: SYSTEMIC CONDITIONS AND SOCIODEMOGRAPHIC FACTORS - Custodio, Lia Borges de Mattos; Saliba, Tania Adas; Saliba, Orlando; Saliba, Nemre Adas; Moimaz, Suzely Adas Saliba (Revista Valore, 2021)
The aim of this research was to investigate the oral health condition of high-risk pregnant women. This was a cross-sectional study carried out in the specialised medical service for high-risk pregnant women from 2016 to 2018. Oral health data were collected in 1500 high-risk pregnant women using a methodology recommended by the World Health Organisation to perform the clinical examination. High-risk pregnant women scheduled for prenatal consultations were included in the present study. The exclusion criteria were refusal by the pregnant woman to participate in the study or inability to perform the oral examination due to excessive nausea or vomiting of the patient. The following variables were analysed: age, income, educational level, arterial hypertension, gestational arterial hypertension, diabetes mellitus, gestational diabetes mellitus, obesity and smoking. Association tests, chi-square, were made at significance level of 5%. After, univariate and multivariate logistic regression analyzes were performed to estimate odds ratio and confidence interval. The Decayed teeth was associated with following variables: income (p=0.00); educational level (p=0.00) arterial hypertension (p=0.01), smoking (p=0.00) and obesity (p=0.00). It was concluded that dental caries have a high prevalence in high-risk pregnant women and are associated with income, educational level, arterial hypertension, smoking and obesity.